Implementasi Metode Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah Boarding School Kampung Sawah - Rizki Amrillah; Ahmad Abimubarok (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Learning methods are an essential component in the implementation of learning in schools. The learning method is a way of conveying a theory or idea to facilitate the process of managing the theory so as to produce a complete understanding and mastery of the subject. If the implementation of Islamic Religious Education learning methods is appropriate, it will have an impact on increasing the values